Nanoliposome-Encapsulated and Non-Encapsulated Phenolics From Achillea millefolium and Their Biological Function in Mice Challenged by Campylobacter jejuni: A Comparative Study - Nateghi, Nikta; Karimi, Ehsan; Oskoueian, Ehsan (Frontiers in Molecular Biosciences, 2022)
The objective of this research was to develop the nanoliposome-encapsulated phenolic rich fraction from Achillea millefolium (A. millefolium) and to investigate its antibacterial and health-promoting activities in mice challenged by pathogenic foodborne Campylobacter jejuni. The A. millefolium was extracted and the ethyl acetate fraction was found to be the phenolic-rich fraction (PRF) containing 14.72±2.39 mg GAE/g DM. The nanoliposome-loaded PRF (PRF-NLs) was synthesized and the particles were in nanometer size (187.2 nm) with homogeneous dispersion (PDI 0.213) and moderate stability behavior in colloidal dispersions (Zeta potential -37.45). The non-encapsulated PRF and PRF-NLs were gavaged orally in the mice for 28 days and mice were challenge with C. jejuni on day 21. The results indicated the dietary supplementation of non-encapsulated PRF and PRF-NLs significantly (p<0.05) improved the average daily weight gain, food intake, liver function, antioxidant status, and morphostructural characteristics of the ileum however the PRF-NLs appeared to be more potent as compared to non-encapsulated PRF. The higher biological activity of PRF-NLs could be associated with the higher intestinal solubility and absorption of nanoliposome-encapsulated PRF. Thereby, the nanoliposome-encapsulated PRF could be considered as a natural antibiotic alternative called phytobiotic to prevent intestinal infection caused by enteropathogenic C. jejuni.